Ab initio study of structural, electronic and thermodynamic properties of Be12V under high temperature. (April 2021) - Liu, Xian-kun; Feng, Qi-Jie; Tang, Bin; Zheng, Zhou
Abstract: The structure, electronic, elasticity and thermodynamic properties, phonon spectra of Be12 V alloy under high temperatures and pressure are investigated by using first-principles calculations based on pseudo-potential plane-wave density functional theory method within using the generalized gradient approximation (GGA) and quasi-harmonic Debye model. The results show that the calculated equilibrium structural parameters of Be12 V are in good agreement with the experiments. Under high pressure, the elastic constant of Be12 V alloy increases with the increase of pressure. The all elastic constants satisfy the Born's mechanical criterion, indicating that Be12 V crystal is dynamic stable under the applied pressure (0 GPã50 GPa), and the pressure has little effect on the electronic properties of Be12 V. The phonon spectra and phonon density of states under pressure from 0 GPa to 50 GPa are presented for the Be12 V and discussed the effects of pressure on some properties. By the quasi-harmonic Debye model, the thermodynamic properties of Be12 V under high temperature and pressure were predicted, and the relationship of heat capacity, thermal expansion coefficient with temperature and pressure was obtained in the range of 0–1300 K and 0–20 GPa, respectively. Highlights: Elastic and thermodynamic properties of tetragonal Be12 V are predicted first time by first principles calculation. Pressure effect on phonon spectrum and electronic properties for Be12 V alloy are predicted first time. Mechanical stability is testified and predicted by analysis of elastic constants in wide pressure range of 0–50 GPa .